2015
DOI: 10.1097/hjh.0000000000000681
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of ambulatory and office blood pressure in the Swiss population

Abstract: a Background: Blood pressure (BP) is known to aggregate in families. Yet, heritability estimates are populationspecific and no Swiss data have been published so far. We estimated the heritability of ambulatory and office BP in a Swiss population-based sample. Methods: The Swiss Kidney Project on Genes inHypertension is a population-based family study focusing on BP genetics. Office and ambulatory BP were measured in 1009 individuals from 271 nuclear families. Heritability was estimated for SBP, DBP, and pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…It was higher for daytime compared with sleep BP and the heritabilities of office beat-to-beat BP were lower compared with those for ambulatory daytime and 24-h BP measurements. These results were in line with the univariate BP heritability estimates we published previously [ 19 ] and similar to other family studies of ambulatory BP conducted in different populations (SBP: ranging from 0.25 to 0.39; DBP: ranging from 0.20 to 0.41) [ 26 29 ]. For example, Fava et al [ 26 ] reported that in 118 Swedish families with 260 siblings (without antihypertensive treatment), heritabilities were significant for ambulatory night-time SBP (37%), DBP (32%), ambulatory daytime SBP (33%), 24-h SBP (30%) and DBP (29%) ( P < 0.05 for all).…”
Section: Discussionsupporting
confidence: 92%
“…It was higher for daytime compared with sleep BP and the heritabilities of office beat-to-beat BP were lower compared with those for ambulatory daytime and 24-h BP measurements. These results were in line with the univariate BP heritability estimates we published previously [ 19 ] and similar to other family studies of ambulatory BP conducted in different populations (SBP: ranging from 0.25 to 0.39; DBP: ranging from 0.20 to 0.41) [ 26 29 ]. For example, Fava et al [ 26 ] reported that in 118 Swedish families with 260 siblings (without antihypertensive treatment), heritabilities were significant for ambulatory night-time SBP (37%), DBP (32%), ambulatory daytime SBP (33%), 24-h SBP (30%) and DBP (29%) ( P < 0.05 for all).…”
Section: Discussionsupporting
confidence: 92%
“…Risk factors for cardiovascular disease, including insulin sensitivity, blood pressure, lipids, cholesterol, anthropometric measures, and obesity have been shown to have significant heritability . However, the heritability of measures of subclinical atherosclerosis have not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has suggested that the heritability of HTN is around 20–60% [35]. Genome-wide association studies (GWASs), especially a recent meta-analysis with large consortia, have been productive in recognition of hypertension susceptibility genes, and more than 200 loci have been identified [615].…”
Section: Introductionmentioning
confidence: 99%